Optimization of 1-glyceryl benzoate production by enzymatic transesterification in organic solvents - Ceni G.; Lerin L. A.; de Conto J. F.; Brancher C. V.; da Silva P. C.; Toniazzo G.; Treichel H.; de Oliveira D.; Oliveira J. V.; Oestreicher E. G.; Antunes O. A. C. (Enzyme and Microbial Technology, 2010)
This work is focused on the evaluation of reaction parameters involved in the enzymatic production of 1-glyceryl benzoate, an intermediate substance to carvedilol and propranolol synthesis, catalyzed by Candida antarctica lipase in different organic solvents. To our knowledge, no related study on this subject is available in the open literature. The main goals of the present investigation were to elucidate the relationship between relevant reaction variables and also to determine the optimum conditions for 1-glyceryl benzoate production. Results showed that the strategy adopted for the experimental design proved to be useful in maximizing the reaction conversion in 2-propanol as solvent with Novozym 435 as catalyst. The optimum conditions were found to be methyl benzoate to glycerol molar ratio of 1:1, stirring rate of 150 rpm, 50 °C, enzyme concentration of 10 wt% at 36 h of reaction, with a resulting conversion to 1-glyceryl benzoate of about 29%. Reaction kinetics of 1-glyceryl benzoate production demonstrated that very satisfactory conversions (∼40%) were achieved after 70 h of reaction. © 2009 Elsevier Inc. All rights reserved.